Case Report: Micafungin for treating Candida glabrata urinary infection: a clinical case in a premature neonate - Parramon-Teixido, Carlos Javier; Garcia Esquerda, Carme; Frick, Marie Antoinette; Tripodi, Cinzia; Gomez-Ganda, Laura; Ruiz-Campillo, Cesar Wenceslao; Cabañas-Poy, Maria Josep (Frontiers in Pediatrics, 2024)
Urinary tract infections (UTIs) associated with indwelling urinary catheterization (IUC) in premature newborns (PNBs) pose a significant challenge in neonatal intensive care units (NICUs) due to the vulnerability of this population to infections and the necessity of invasive procedures. While bacterial UTIs have historically been predominant, there is a rising incidence of fungal pathogens, particularly non-albicans Candida strains like C. glabrata and C. tropicalis, attributed to broad-spectrum antibiotic use. Diagnosis of fungal UTIs in a PNB relies on culturing Candida spp. from properly collected urine samples, particularly critical in very low birth weight (VLBW) PNBs because of the risk of invasive candidiasis and associated complications. We present a case of an extremely premature newborn (EPNB) successfully treated for a UTI caused by Candida glabrata with micafungin. Our case exhibits micafungin as a potentially safe and effective alternative for treating Candida glabrata UTIs in neonates.Micafungin dosing recommendations for neonatal candidemia are well-established, but dosing for candiduria remains uncertain. Recent studies suggest a dose of 2 mg/kg/day may be efficacious in pediatric patients, although no consensus exists for neonates. Despite extensive evidence supporting micafungin use in treating fungal UTIs in adults, data in neonates are scarce, highlighting the need for research in this population. Our case exhibits micafungin as a potentially safe and effective alternative for treating Candida glabrata UTIs in neonates, though additional studies are required to validate its efficacy and safety in this vulnerable population.In conclusion, micafungin could be an adequate therapeutic option for neonatal UTIs caused by Candida glabrata, offering the potential for yeast eradication and patient recovery.Integration of pharmacists into clinical teams can aid in optimizing treatment strategies, emphasizing the importance of interdisciplinary collaboration in neonatal care.